2016
DOI: 10.1016/j.biocon.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Limited erosion of genetic and species diversity from small forest patches: Sacred forest groves in an Afrotropical biodiversity hotspot have high conservation value for butterflies

Abstract: Sacred forest groves are often located in some of the world's hottest hotspots of biodiversity, and consequently have high potential conservation value. Recent efforts to quantify their value have focused nearly exclusively on a single component of diversity, species diversity within communities, which may or may not be an effective proxy for a second fundamental component of diversity, genetic diversity within populations. We studied fruit-feeding butterfly communities to simultaneously assess to what extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Furthermore, they can provide a source for rural afforestation and play a key role in ecological networks. Globally, CPFs are distinctive elements of worldwide vegetations, and they naturally and seminaturally distribute in and around urban areas (Avtzis et al, ; Bossart & Antwi, ; Hu et al, ; Lee et al, ). Similar to Feng Shui woodlands in China, most of the plant species in CPFs are not considered being threatened in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they can provide a source for rural afforestation and play a key role in ecological networks. Globally, CPFs are distinctive elements of worldwide vegetations, and they naturally and seminaturally distribute in and around urban areas (Avtzis et al, ; Bossart & Antwi, ; Hu et al, ; Lee et al, ). Similar to Feng Shui woodlands in China, most of the plant species in CPFs are not considered being threatened in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…They are important rural/urban forest types worldwide including Asia, Africa, Europe, and Latin America. They are known as Feng Shui woodlands in China (Ye, Xu, Wu, & Cao, ) and sacred groves (Avtzis et al, ; Bossart & Antwi, ) and village groves (Lee, Hong, & Kim, ) in the other countries. They are generally small in size but can serve as refuges for a large number of regional species (Avtzis et al, ; Bossart & Antwi, ; Hu et al, ; Lee et al, ; Martinez & Amar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates in Ghana suggest there are 2000-3200 such sacred sites [141]. Studies within sacred groves on the Accra Plains found that the biomass and diversity of small mammals often exceed that of surrounding biomes [141]; similar correlations have also been made more recently regarding butterfly populations [142]. In the Loma area in Liberia, dominated by the Upper Guinea forests, sacred areas are often the sites of old towns or graves and the long history and mobility of people and settlements has created a dense network of such sacred areas [143].…”
Section: Place-based Memoriesmentioning
confidence: 84%
“…These culturally protected forests are manifestations of traditional Chinese spatial concepts of beauty and are referred to as village fengshui forests. As heterogeneous habitat spaces, they likely harbour greater insect diversity than surrounding areas and certainly promote regional biodiversity [ 192 , 193 ]. Further research will demonstrate the relationship between these culturally protected forests and butterfly diversity.…”
Section: Recommendations Of Future Butterfly Conservationmentioning
confidence: 99%